Winter conference in summer: report on the International Conference on Conversation Analysis (ICCA) from June 26th to July 2nd 2023 in Brisbane/Meanjin (Australia) - Kornfeld, Laurenz; Mack, Christina; Rogowska, Jowita; Schubert, Mojenn (Göttingen : Verlag für Gesprächsforschung, 2023)
From June 26th to July 2nd 2023 the International Conference on Conversation Analysis (ICCA) took place in Brisbane/Meanjin, Australia – after a long pause due to the Covid-pandemic and for the first time in the southern hemisphere. About 350 participants from about 50 different countries attended the conference. This year’s ICCA came up with 36 panels and about 300 papers that were presented. Four plenary speakers have been invited and 24 pre-conference workshops took place. On Wednesday evening Ilana Mushin, in her role as conference chair, officially opened ICCA. The President of the International Society of Conversation Analysis (ISCA), Tanya Stivers, also welcomed all participants. To get acquainted with the indigenous culture of Queensland, the opening ceremony was enriched with a highly impressive dance performance by First Nations people. After the official inauguration the international community met at the Welcome Reception to look forward together to the days ahead with many opportunities for exchange and networking. As it will become clear throughout this report, the research topics revolved around not only classic CA concepts, but also importantly concerned embodiment, which continued the line of past conferences (Dix 2019). Another aspect that has been highlighted was conflict and social norms. Due to personal capacities, we can only present a selection of presentations within the scope of this conference report. The selection was influenced by the personal interest of the authors and should not be understood as rating in any sense.